Improved composite magnesium-based hydrogen storage material based on graphene oxide doped zr-v bimetallic oxide and preparation method and application thereof
Patent Information
- Application Number
- CN202411099125.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-08-12
AI Technical Summary
然而,氢化镁过高的热力学稳定性使其实际使用温度高于300℃,而且吸放氢速率缓慢,这直接限制了其产业化应用
[0025]1、本发明公开了一种基于氧化石墨烯掺杂的Zr-V双金属氧化物改善的复合镁基储氢材料,该复合镁基储氢材料包括质量百分比为3~15wt%的氧化石墨烯掺杂的Zr-V双金属氧化物和MgH2材料,具有以下优点:一方面,氧化石墨烯掺杂的Zr-V双金属氧化物中Zr-V双金属氧化物在吸放氢过程中被破碎并还原为低价态的物相(如ZrH2、V2O3)后分散在MgH2材料中作为活性位点,能够促进氢的解离、扩散和结合,故Zr-V双金属氧化物的添加为体系创造了一个多相、多界面的协同催化环境;另一方面,氧化石墨烯掺杂的Zr-V双金属氧化物中氧化石墨烯的物理掺杂可以作为额外的电子转移介质,加快了吸放氢过程中Mg-H键和H-H键的断裂和结合。因此,MgH2材料经过氧化石墨烯掺杂的Zr-V双金属氧化物的催化,可实现以下技术效果:(1)显著降低了镁基储氢材料的初始放氢温度;(2)显著提升放氢速度;(3)显著提升了吸氢速率。
Smart Images

Figure CN118929571B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnesium-based hydrogen storage material preparation technology, and relates to composite magnesium-based hydrogen storage materials improved by Zr-V bimetallic oxide doped with graphene oxide, their preparation methods and applications. Background Technology
[0002] With the global energy shortage and escalating environmental problems, developing sustainable and clean new energy sources is one of the most pressing issues facing the world today. Hydrogen energy, with its abundant sources, cleanliness, and high energy density, is considered one of the most promising new energy sources. Currently, the key technological bottleneck restricting the development of the hydrogen energy industry is the safe and efficient storage and transportation of hydrogen.
[0003] Solid-state hydrogen storage technology based on metal hydrides not only has high volumetric hydrogen storage density, but also significantly improves the safety of hydrogen storage and transportation compared to traditional hydrogen storage methods.
[0004] Magnesium hydride (MgH2) possesses advantages such as high hydrogen storage density, low cost, and good cycle stability, making it one of the most promising solid-state hydrogen storage materials. However, its excessively high thermodynamic stability limits its practical operating temperature to above 300°C, and its slow hydrogen absorption and desorption rates directly restrict its industrial application. Catalyst doping is a highly efficient solution to improve the performance of MgH2. Adding trace amounts of catalyst can significantly lower the hydrogen absorption and desorption temperatures of MgH2 and effectively reduce the kinetic energy barrier of the hydrogen storage system, thereby promoting an increase in absorption and desorption rates.
[0005] Therefore, developing a dopant with high catalytic activity is of great significance for improving the hydrogen storage performance of magnesium hydride. Summary of the Invention
[0006] In view of this, one objective of the present invention is to provide a composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide doped with graphene oxide; a second objective of the present invention is to provide a method for preparing the composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide doped with graphene oxide; and a third objective of the present invention is to provide an application of the composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide doped with graphene oxide in solid-state hydrogen storage.
[0007] To achieve the above objectives, the present invention provides the following technical solution:
[0008] 1. A composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide, wherein the composite magnesium-based hydrogen storage material comprises graphene oxide-doped Zr-V bimetallic oxide and MgH2 material, wherein the mass percentage of graphene oxide-doped Zr-V bimetallic oxide in the composite magnesium-based hydrogen storage material is 3 to 15 wt%.
[0009] Preferably, the graphene oxide-doped Zr-V bimetallic oxide is prepared according to the following method:
[0010] (1) Preparation of Zr-V bimetallic oxide: Ammonium metavanadate, zirconium tetrachloride and urea were dissolved in deionized water, stirred and heated to dissolve and mix to obtain a homogeneous solution. After hydrothermal reaction, the solution was centrifuged and freeze-dried to obtain precursor powder. After calcination, Zr-V bimetallic oxide material was obtained.
[0011] (2) Preparation of graphene oxide-doped Zr-V bimetallic oxide: Zr-V bimetallic oxide and graphene oxide dispersion are mixed evenly and ball-milled under an inert gas atmosphere to obtain graphene oxide-doped Zr-V bimetallic oxide.
[0012] More preferably, in step (1), the stirring and heating temperature is 70-90°C, and the molar ratio of ammonia metavanadate, zirconium tetrachloride and urea is 2.0:1.0:2.0-2.6:1.0:5.0.
[0013] More preferably, in step (1), the hydrothermal reaction specifically involves a hydrothermal reaction at 180–220°C for 8–12 hours.
[0014] More preferably, in step (1), the calcination temperature is 480℃~550℃ and the time is 2~5h.
[0015] More preferably, in step (2), the mass fraction of graphene oxide in the graphene oxide dispersion is 0.3wt% to 0.7wt%, and the solvent in the graphene oxide dispersion is pure water;
[0016] The mass ratio of graphene oxide in the Zr-V bimetallic oxide and graphene oxide dispersion is 0.90:0.10 to 0.99:0.01.
[0017] More preferably, in step (2), the inert gas is argon or nitrogen;
[0018] The ball-to-material ratio during the ball milling process is 10:1 to 20:1, the ball milling speed is 150 to 250 rpm, and the ball milling time is 2 to 5 hours.
[0019] 2. According to the above-mentioned preparation method of composite magnesium-based hydrogen storage material, the specific preparation method is as follows:
[0020] A composite magnesium-based hydrogen storage material improved by graphene-doped Zr-V bimetallic oxide can be obtained by uniformly mixing graphene oxide-doped Zr-V bimetallic oxide and MgH2 material and ball milling under an argon or hydrogen atmosphere.
[0021] Preferably, the mass ratio of the graphene oxide-doped Zr-V bimetallic oxide to the MgH2 material is 0.03:0.97 to 0.85:0.15;
[0022] The ball-to-material ratio during the ball milling process is 20:1 to 30:1, the ball milling speed is 350 to 400 rpm, and the ball milling time is 8 to 12 hours.
[0023] 3. Application of the above-mentioned composite magnesium-based hydrogen storage materials improved by Zr-V bimetallic oxide doped with graphene oxide in solid-state hydrogen storage.
[0024] The beneficial effects of this invention are as follows:
[0025] 1. This invention discloses a composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide. This composite magnesium-based hydrogen storage material comprises 3–15 wt% graphene oxide-doped Zr-V bimetallic oxide and MgH2 material, and has the following advantages: On the one hand, during hydrogen absorption and desorption, the Zr-V bimetallic oxide in the graphene oxide-doped Zr-V bimetallic oxide is broken down and reduced to low-valence phases (such as ZrH2 and V2O3), which are then dispersed in the MgH2 material as active sites, promoting the dissociation, diffusion, and binding of hydrogen. Therefore, the addition of Zr-V bimetallic oxide creates a multiphase, multi-interface synergistic catalytic environment for the system. On the other hand, the physical doping of graphene oxide in the graphene oxide-doped Zr-V bimetallic oxide can act as an additional electron transfer medium, accelerating the breaking and binding of Mg-H bonds and HH bonds during hydrogen absorption and desorption. Therefore, the following technical effects can be achieved by catalyzing Zr-V bimetallic oxide doped with graphene oxide in MgH2 material: (1) significantly reducing the initial hydrogen release temperature of magnesium-based hydrogen storage materials; (2) significantly increasing the hydrogen release rate; and (3) significantly increasing the hydrogen absorption rate.
[0026] 2. This invention also discloses a method for preparing a composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide. First, Zr-V bimetallic oxide is prepared by hydrothermal-calcination method, then graphene oxide-doped Zr-V bimetallic oxide is prepared by ball milling, and finally, the composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide is prepared by mechanical ball milling and mixing with MgH2 material. This preparation method is simple and easy to operate, and can meet the industrial application requirements of magnesium-based hydrogen storage materials.
[0027] Other advantages, objectives, and features of the invention will be set forth in part in the description which follows, and in part will be apparent to those skilled in the art from the following examination, or may be learned from practice of the invention. The objectives and other advantages of the invention can be realized and obtained through the following description. Attached Figure Description
[0028] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred embodiments of the present invention will be described in detail below with reference to the accompanying drawings, wherein:
[0029] Figure 1 SEM image of the Zr-V bimetallic oxide prepared in Example 1;
[0030] Figure 2 This is a TEM image of the graphene oxide-doped Zr-V bimetallic oxide prepared in Example 2.
[0031] Figure 3 The hydrogen desorption curve (TPD) of the Zr-V bimetallic oxide-doped composite magnesium-based hydrogen storage material prepared in Example 3 is shown.
[0032] Figure 4 The isothermal hydrogen desorption curve of the composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide based on graphene oxide doping prepared in Example 3 is shown.
[0033] Figure 5 The isothermal hydrogen absorption curves of the composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide doped with graphene oxide prepared in Example 3 are shown. Detailed Implementation
[0034] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Unless otherwise specified, the following embodiments and features can be combined with each other.
[0035] Example 1:
[0036] A Zr-V bimetallic oxide is prepared by the following method:
[0037] 2.3 mmol of ammonium metavanadate, 1 mmol of zirconium tetrachloride, and 3.8 mmol of urea were dissolved in 60 mL of deionized water and heated to 80 °C in a water bath with stirring until fully dissolved to obtain a homogeneous mixed solution. The mixed solution was transferred to a 60 mL polytetrafluoroethylene-lined reactor and hydrothermally reacted at 200 °C for 12 h. After centrifugation, washing, and freeze-drying to remove moisture, Zr-V bimetallic oxide precursor powder was obtained. The Zr-V bimetallic oxide precursor powder was calcined in air for 2 h (calcination temperature was 525 °C) to obtain the Zr-V bimetallic oxide material.
[0038] The SEM image of the Zr-V bimetallic oxide prepared in Example 1 above is shown below. Figure 1 As shown. From Figure 1 As can be seen, Zr-V bimetallic oxide is a bulk structure composed of nanoparticles with a size of 70-120 nm.
[0039] Example 2:
[0040] A graphene oxide-doped Zr-V bimetallic oxide (ZrVO@GO) is prepared using the following method:
[0041] Take 0.9875g of Zr-V bimetallic oxide (ZrV2O7) powder and 2.5mL of graphene oxide dispersion (obtained by dissolving 0.1g of graphene oxide in 20mL of pure water solvent) and place them in a stainless steel ball mill jar for mechanical mixing. The ball milling atmosphere is high-purity argon, the ball milling speed is 250rpm, and the ball-to-material ratio is 15:1. Install the ball mill jar on a planetary ball mill and ball mill for 2 hours. After every 20 minutes of ball milling, stop the machine for 10 minutes to obtain graphene-doped Zr-V bimetallic oxide (ZrVO@GO).
[0042] TEM images of the graphene oxide-doped Zr-V bimetallic oxide prepared in Example 2 above are shown below. Figure 2 As shown. From Figure 2 It can be seen that the Zr-V bimetallic oxide particles and graphene oxide nanosheets in the graphene oxide-doped Zr-V bimetallic oxide are in a physically mixed state, and the size range of the Zr-V bimetallic oxide particles is 70-180 nm.
[0043] Example 3:
[0044] A composite magnesium-based hydrogen storage material (+ZrVO@GO) improved by graphene oxide-doped Zr-V bimetallic oxide is prepared as follows:
[0045] 0.940 g of MgH2 powder and 0.060 g of graphene oxide-doped Zr-V bimetallic oxide were placed in a stainless steel ball mill jar for high-energy ball milling. The ball milling atmosphere was high-purity argon, the ball milling speed was 400 rpm, and the ball-to-material ratio was 30:1. After every 10 minutes of ball milling, the machine was stopped and rested for 10 minutes. The ball mill jar was installed on a planetary ball mill and ball milled for 12 hours to obtain a composite magnesium-based hydrogen storage material (+ZrVO@GO) improved by graphene oxide-doped Zr-V bimetallic oxide.
[0046] The temperature-dependent hydrogen desorption (TPD) curves of the composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide prepared in Example 3 above are shown below. Figure 3 As shown. From Figure 3 As can be seen from the data, the initial hydrogen desorption temperature of the composite magnesium-based hydrogen storage material (+ZrVO@GO) prepared in Example 3 based on graphene oxide-doped Zr-V bimetallic oxide improved is 195℃, which is significantly lower than the 305℃ of the MgH2 material (ball-milled MgH2) used in the preparation process by 36.1%.
[0047] The isothermal hydrogen desorption curve of the composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide prepared in Example 3 above is shown in the figure. Figure 4 As shown. From Figure 4 It can be seen that, at 300℃ for 5 minutes, the hydrogen release rates of the composite magnesium-based hydrogen storage material improved by graphene-doped Zr-V bimetallic oxide (+ZrVO@GO) and the MgH2 material (ball-milled MgH2) were 6.0 wt% and 0.3 wt%, respectively. This indicates that the hydrogen release rate of the composite magnesium-based hydrogen storage material improved by graphene-doped Zr-V bimetallic oxide at 300℃ for 5 minutes is 20 times that of the MgH2 material. Therefore, adding graphene-doped Zr-V bimetallic oxide to the MgH2 material can significantly improve its hydrogen release rate.
[0048] The isothermal hydrogen absorption curves of the composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide prepared in Example 3 above are shown below. Figure 5 As shown. From Figure 5It can be seen that, at 125℃ for 30 min, the hydrogen absorption capacities of the composite magnesium-based hydrogen storage material improved by graphene-doped Zr-V bimetallic oxide (+ZrVO@GO) and the MgH2 material (ball-milled MgH2) were 5.7 wt% and 0.6 wt%, respectively. Furthermore, at 75℃ and 250℃, the hydrogen absorption capacities of the composite magnesium-based hydrogen storage material improved by graphene-doped Zr-V bimetallic oxide reached 4.2 wt% and 6.2 wt%, respectively, within 30 min. Therefore, adding graphene-doped Zr-V bimetallic oxide to the MgH2 material can significantly improve its hydrogen absorption rate.
[0049] Example 4
[0050] A Zr-V bimetallic oxide is prepared by the following method:
[0051] 2.0 mmol of ammonium metavanadate, 1 mmol of zirconium tetrachloride, and 2.0 mmol of urea were dissolved in 60 mL of deionized water and heated to 70 °C in a water bath with stirring until fully dissolved to obtain a homogeneous mixed solution. The mixed solution was transferred to a 60 mL polytetrafluoroethylene-lined reactor and hydrothermally reacted at 180 °C for 12 h. After centrifugation, washing, and freeze-drying to remove moisture, Zr-V bimetallic oxide precursor powder was obtained. The Zr-V bimetallic oxide precursor powder was calcined in air for 2 h (calcination temperature was 550 °C) to obtain Zr-V bimetallic oxide material.
[0052] Example 5
[0053] A Zr-V bimetallic oxide is prepared by the following method:
[0054] 2.6 mmol of ammonium metavanadate, 1 mmol of zirconium tetrachloride, and 5.0 mmol of urea were dissolved in 60 mL of deionized water and heated to 90 °C in a water bath with stirring until fully dissolved to obtain a homogeneous mixed solution. The mixed solution was transferred to a 60 mL polytetrafluoroethylene-lined reactor and hydrothermally reacted at 220 °C for 8 h. After centrifugation, washing, and freeze-drying to remove moisture, Zr-V bimetallic oxide precursor powder was obtained. The Zr-V bimetallic oxide precursor powder was calcined in air for 5 h (calcination temperature was 480 °C) to obtain the Zr-V bimetallic oxide material.
[0055] Example 6
[0056] A graphene oxide-doped Zr-V bimetallic oxide (ZrVO@GO) is prepared using the following method:
[0057] Take 0.98g of Zr-V bimetallic oxide (ZrV2O7) powder and 2.5mL of graphene oxide dispersion (obtained by dissolving 0.16g of graphene oxide in 20mL of pure water solvent) and place them in a stainless steel ball mill jar for mechanical mixing. The ball milling atmosphere is high-purity argon, the ball milling speed is 150rpm, and the ball-to-material ratio is 20:1. Install the ball mill jar on a planetary ball mill and ball mill for 5h. After every 20min of ball milling, stop and rest for 10min to obtain graphene-doped Zr-V bimetallic oxide (ZrVO@GO).
[0058] Example 7
[0059] A graphene oxide-doped Zr-V bimetallic oxide (ZrVO@GO) is prepared using the following method:
[0060] Take 0.95g of Zr-V bimetallic oxide (ZrV2O7) powder and 2.5mL of graphene oxide dispersion (obtained by dissolving 0.4g of graphene oxide in 20mL of pure water solvent) and place them in a stainless steel ball mill jar for mechanical mixing. The ball milling atmosphere is high-purity argon, the ball milling speed is 200rpm, and the ball-to-material ratio is 10:1. Install the ball mill jar on a planetary ball mill and ball mill for 4 hours. After every 20 minutes of ball milling, stop the machine for 10 minutes to rest. Graphene oxide-doped Zr-V bimetallic oxide (ZrVO@GO) can be obtained.
[0061] Example 8
[0062] A composite magnesium-based hydrogen storage material (+ZrVO@GO) improved by graphene oxide-doped Zr-V bimetallic oxide is prepared as follows:
[0063] 0.97g of MgH2 powder and 0.03g of graphene oxide-doped Zr-V bimetallic oxide were placed in a stainless steel ball mill jar for high-energy ball milling. The ball milling atmosphere was high-purity argon, the ball milling speed was 350 rpm, and the ball-to-material ratio was 20:1. The ball milling was stopped and rested for 10 minutes after every 10 minutes of operation. The ball mill jar was installed on a planetary ball mill and milled for 8 hours to obtain a composite magnesium-based hydrogen storage material (+ZrVO@GO) improved by graphene oxide-doped Zr-V bimetallic oxide.
[0064] Example 9
[0065] A composite magnesium-based hydrogen storage material (+ZrVO@GO) improved by graphene oxide-doped Zr-V bimetallic oxide is prepared as follows:
[0066] 0.85g of MgH2 powder and 0.15g of graphene oxide-doped Zr-V bimetallic oxide were placed in a stainless steel ball mill jar for high-energy ball milling. The ball milling atmosphere was high-purity argon, the ball milling speed was 350rpm, and the ball-to-material ratio was 25:1. After every 10 minutes of ball milling, the machine was stopped and rested for 10 minutes. The ball mill jar was installed on a planetary ball mill and ball milled for 10 hours to obtain a composite magnesium-based hydrogen storage material (+ZrVO@GO) improved by graphene oxide-doped Zr-V bimetallic oxide.
[0067] Similarly, the Zr-V bimetallic oxides prepared in Examples 4 and 5 were subjected to the same structural and performance tests as those prepared in Example 1. The results showed that the structure and performance were similar to those of the Zr-V bimetallic oxide prepared in Example 1, indicating that the preparation method of the present invention can indeed prepare Zr-V bimetallic oxides. The graphene oxide-doped Zr-V bimetallic oxides (ZrVO@GO) prepared in Examples 6 and 7 were subjected to the same structural and performance tests as those prepared in Example 2. The results showed that the structure and performance were similar to those of the graphene oxide-doped Zr-V bimetallic oxides (ZrVO@GO) prepared in Example 2, indicating that the preparation method of the present invention can indeed prepare graphene oxide-doped Zr-V bimetallic oxides (ZrVO@GO). The graphene oxide-doped Zr-V bimetallic oxides prepared in Examples 8 and 9 were also tested. The composite magnesium-based hydrogen storage material (+ZrVO@GO) improved by Zr-V bimetallic oxide was subjected to the same structural and performance tests as the graphene-doped Zr-V bimetallic oxide-improved composite magnesium-based hydrogen storage material (+ZrVO@GO) prepared in Example 3. The results showed that the structure and performance were similar to those of the graphene-doped Zr-V bimetallic oxide-improved composite magnesium-based hydrogen storage material (+ZrVO@GO) prepared in Example 3 (the initial hydrogen release temperature was significantly lower than that of MgH2 material (ball-milled MgH2) at 300°C within 5 min, the hydrogen release amount was significantly greater than that of MgH2 material (ball-milled MgH2) by 0.3 wt%, and the hydrogen absorption amount was significantly greater than that of MgH2 material (ball-milled MgH2) within 30 min at 125°C by 0.6 wt%). This indicates that the preparation method of the present invention can indeed prepare the graphene-doped Zr-V bimetallic oxide-improved composite magnesium-based hydrogen storage material (+ZrVO@GO).
[0068] In summary, this invention discloses a composite magnesium-based hydrogen storage material improved by graphene oxide-doped Zr-V bimetallic oxide. This composite magnesium-based hydrogen storage material comprises 3–15 wt% graphene oxide-doped Zr-V bimetallic oxide and MgH2 material, and has the following advantages: Firstly, during hydrogen absorption and desorption, the Zr-V bimetallic oxide in the graphene oxide-doped Zr-V bimetallic oxide is broken down and reduced to low-valence phases (such as ZrH2 and V2O3), which are then dispersed in the MgH2 material as active sites, promoting hydrogen dissociation, diffusion, and binding. Therefore, the addition of Zr-V bimetallic oxide creates a multiphase, multi-interface synergistic catalytic environment for the system. Secondly, the physical doping of graphene oxide in the graphene oxide-doped Zr-V bimetallic oxide can act as an additional electron transfer medium, accelerating the breaking and binding of Mg-H bonds and HH bonds during hydrogen absorption and desorption. Therefore, the following technical effects can be achieved by catalyzing MgH2 material with Zr-V bimetallic oxide doped with graphene oxide: (1) significantly reducing the initial hydrogen release temperature of magnesium-based hydrogen storage materials; (2) significantly increasing the hydrogen release rate; and (3) significantly increasing the hydrogen absorption rate. In addition, this invention also discloses a method for preparing a composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide doped with graphene oxide. First, Zr-V bimetallic oxide is prepared by hydrothermal-calcination method, then Zr-V bimetallic oxide doped with graphene oxide is prepared by ball milling, and finally, the composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide doped with graphene oxide is prepared by mechanical ball milling and mixing. This preparation method is simple and easy to operate, and can meet the industrial application requirements of magnesium-based hydrogen storage materials.
[0069] The above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A composite magnesium-based hydrogen storage material improved by Zr-V bimetallic oxide doped with graphene oxide, characterized in that, The composite magnesium-based hydrogen storage material comprises graphene oxide-doped Zr-V bimetallic oxide and MgH2 material, wherein the mass percentage of graphene oxide-doped Zr-V bimetallic oxide in the composite magnesium-based hydrogen storage material is 3~15 wt%. The graphene oxide-doped Zr-V bimetallic oxide was prepared according to the following method: (1) Preparation of Zr-V bimetallic oxide: Ammonium metavanadate, zirconium tetrachloride and urea were dissolved in deionized water, stirred and heated to dissolve and mix to obtain a homogeneous solution. After hydrothermal reaction, the solution was centrifuged and freeze-dried to obtain precursor powder. After calcination, Zr-V bimetallic oxide material was obtained. (2) Preparation of graphene oxide-doped Zr-V bimetallic oxide: Zr-V bimetallic oxide and graphene oxide dispersion are mixed evenly and ball-milled under an inert gas atmosphere to obtain graphene oxide-doped Zr-V bimetallic oxide.
2. The composite magnesium-based hydrogen storage material according to claim 1, characterized in that, In step (1), the stirring and heating temperature is 70~90℃, and the molar ratio of ammonia metavanadate, zirconium tetrachloride and urea is 2.0:1.0:2.0~2.6:1.0:5.
0.
3. The composite magnesium-based hydrogen storage material according to claim 1, characterized in that, In step (1), the hydrothermal reaction specifically involves a hydrothermal reaction at 180~220℃ for 8~12 h.
4. The composite magnesium-based hydrogen storage material according to claim 1, characterized in that, In step (1), the calcination temperature is 480℃~550℃ and the time is 2~5 h.
5. The composite magnesium-based hydrogen storage material according to claim 1, characterized in that, In step (2), the mass fraction of graphene oxide in the graphene oxide dispersion is 0.3 wt%~0.7 wt%, and the solvent in the graphene oxide dispersion is pure water; The mass ratio of graphene oxide in the Zr-V bimetallic oxide and graphene oxide dispersion is 0.90:0.10~0.99:0.
01.
6. The composite magnesium-based hydrogen storage material according to claim 1, characterized in that, In step (2), the inert gas is argon or nitrogen; The ball-to-material ratio during the ball milling process is 10:1 to 20:1, the ball milling speed is 150 to 250 rpm, and the ball milling time is 2 to 5 hours.
7. The method for preparing the composite magnesium-based hydrogen storage material according to any one of claims 1 to 6, characterized in that, The composite magnesium-based hydrogen storage material is obtained by uniformly mixing graphene oxide-doped Zr-V bimetallic oxide and MgH2 material at a mass ratio of 0.03:0.97~0.15:0.85 and ball milling under an argon or hydrogen atmosphere. During the ball milling process, the ball-to-material ratio is 20:1~30:1, the ball milling speed is 350~400 rpm, and the ball milling time is 8~12 h.
8. The application of the composite magnesium-based hydrogen storage material based on graphene oxide-doped Zr-V bimetallic oxide improved by any one of claims 1 to 6 in solid-state hydrogen storage.
Citation Information
Patent Citations
Hydrogen storage composite material MgH2-Ni-rGO and method for preparing same
CN106395742A
Bimetal composite catalyst for hydrolysis hydrogen production and preparation method thereof
CN117123228A
